PENINGKATAN LITERASI DAN KAPASITAS PENANGGULANGAN BENCANA BERBASIS VIDEO ANIMASI DI KOMUNITAS PAUD TERPADU ALLIFA, SLEMAN - Renindya Azizza Kartikakirana; Gardyas Bidari Adninda; Erfina Nurussa'adah; Cakra Artandra Suryadharma; Rafi Rizkyantara; Muhammad Ahnaf Fairuz; Ahmad Budi Utomo (Universitas Mataram, 2026)
Children in early childhood are a vulnerable group during disasters. Early childhood is expected to have knowledge and skills in disaster mitigation, and this can be obtained, among other things, from Early Childhood Education (PAUD) institutions. In schools, teachers play a crucial role in providing information on disaster management. However, the problem is often that teachers lack this knowledge and this skill. This phenomenon also occurred at the Allifa Integrated PAUD in Sleman Regency. The objectives of this activity are: 1) to provide knowledge about disaster management and the importance of understanding it for children; 2) to provide learning media for disaster management in the form of animated videos; and 3) to practice disaster management skills. The community service methods used include outreach, technology application, and training. The outreach focused on disaster management. The technology application involved creating animated videos. The training involved practising earthquake disaster management simulations in schools. The community service, specifically outreach, increased partners' knowledge in disaster management from 23% to 91%. The use of animated videos as learning media facilitates the transfer of knowledge and skills to partners. Simulation training was conducted to familiarise students and teachers with earthquake disaster mitigation. During the training, the animated video was played before the disaster simulation practice. Based on observations, students and teachers practised the instructions in the animated video, such as taking cover under tables, protecting their heads, remaining calm/not panicking, following the teacher's directions, and immediately moving to the assembly point. The animated video-based outreach, training, and learning activities improved partners' knowledge and skills in disaster management.